Change in diaphragmatic morphology in single-lung transplant recipients: a computed tomographic study - Touchon, François; Bermudez, Julien; Habert, Paul; Bregeon, Fabienne; Thomas, Pascal Alexandre; Reynaud-Gaubert, Martine; Coiffard, Benjamin (Frontiers in Physiology, 2023)
The influence of lung disease on the diaphragm has been poorly studied. The study aimed to evaluate the diaphragm morphology (height and thickness) in single-lung transplantation (SLTx), using computed tomography (CT), by assessing the evolution of the hemidiaphragm of the transplanted and the native side.Methods: Patients who underwent single lung transplantation in our center (Marseille, France) between January 2009 and January 2022 were retrospectively included. Thoracic or abdominal CT scans performed before and the closest to and at least 3 months after the surgery were used to measure the diaphragm crus thickness and the diaphragm dome height.Results: 31 patients mainly transplanted for emphysema or pulmonary fibrosis were included. We demonstrated a significant increase in diaphragm crus thickness on the side of the transplanted lung, with an estimated difference of +1.25mm, p=<0.001, at the level of the celiac artery, and +0.90mm, p<0.001, at the level of the L1 vertebra while no significant difference was observed on the side of the native lung. We showed a significant reduction in the diaphragm height after SLTx on the transplanted side (-1.20cm, p=0.05), while no change on the native side (+0.02cm, p=0.88).After a SLTx, diaphragmatic morphology significantly changed on the transplanted lung, while remaining altered on the native lung. These results highlights that an impaired lung may have a negative impact on its diaphragm. Replacement with a healthy lung can promote the recovery of the diaphragm to its anatomical morphology, reinforcing the close relationship between these two organs.